معوقات تسويق الخدمات المصرفية الالكترونية في المصارف التجارية دراسة تطبيقية على مصرف الجمهورية بمدينة طرابلس (Economic studies journal, 2022)
This study aimed to identify the obstacles (technical, technical, security, and administrative) that hinder the marketing of electronic banking services in commercial banks. Their number was (230) individuals, while the study sample consisted of (144) individuals. The questionnaire forms were distributed to all members of the sample. The number of the recovered forms reached (117) out of the total number of distributed forms, which amounted to (144) questionnaires, i.e. a response rate ( 81.25%), and the data of the study was analyzed using the SPSS statistical package program. The necessity of providing the appropriate information infrastructure in terms of computer hardware, software, telecommunications services and the Internet, and solving the problem of slow Internet and continuous network disruption.
Keywords: Obstacles; electronic marketing; electronic banking services; commercial banks